Sampling, characterisation and processing of solid recovered fuel production from municipal solid waste: An Italian plant case study. Issue 8 (August 2017) - Ranieri, Ezio; Ionescu, Gabriela; Fedele, Arcangela; Palmieri, Eleonora; Ranieri, Ada Cristina; Campanaro, Vincenzo
This article presents the classification of solid recovered fuel from the Massafra municipal solid waste treatment plant in Southern Italy in compliancy with the EN 15359 standard. In order to ensure the reproducibility of this study, the characterisation methods of waste input and output flow, the mechanical biological treatment line scheme and its main parameters for each stage of the processing chain are presented in details, together with the research results in terms of mass balance and derived fuel properties. Under this study, only 31% of refused municipal solid waste input stream from mechanical biological line was recovered as solid recovered fuel with a net heating value (NC=HV) average of 15.77 MJ kg −1 ; chlorine content average of 0.06% on a dry basis; median of mercury <0.0064 mg MJ −1 and 80th percentile <0.0068 mg MJ −1 . The solid recovered fuel produced meets the European Union standard requirements and can be classified with the class code: Net heating value (3); chlorine (1); mercury (1).